The heart healthy lenoir project-an intervention to reduce disparities in hypertension control: Study protocol - Halladay, Jacquie R; Donahue, Katrina E.; Hinderliter, Alan L; Cummings, Doyle M.; Cené, Crystal W.; Miller, Cassie L; Garcia, Beverly A; Tillman, Jim; DeWalt, Darren A.; Heart Healthy Lenoir Research Team (My University, 2013)
Background Racial disparities in blood pressure control are well established; however the impact of low health literacy (LHL) on blood pressure has garnered less attention. Office based interventions that are created with iterative patient, practice and community stakeholder input and are rolled out incrementally, may help address these disparities in hypertension control. This paper describes our study protocol. Methods/design Using a community based participatory research (CBPR) approach, we designed and implemented a cohort study that includes both a practice level and patient level intervention to enhance the care and support of patients with hypertension in primary care practices in a rural region of eastern North Carolina. The study is divided into a formative phase and an ongoing 2.5 year implementation phase. Our main care enhancement activities include the integration of a community health coach, using home blood pressure monitoring in clinical decision making, standardizing care delivery processes, and working to improve medication adherence. Main outcomes include overall blood pressure change, the differential change in blood pressure by race (African American vs. White) and health literacy level (low vs. higher health literacy). Discussion Using a community based participatory approach in primary care practice settings has helped to engage patients and practice staff and providers in the research effort and in making practice changes to support hypertension care. Practices have engaged at varying levels, but progress has been made in implementing and iteratively improving upon the interventions to date.
Keywords: Hypertension, Methods, Quality improvement, Disparities, Community based participatory research